Sensitive and selective colorimetric detection of Hg2+ by a Hg2+ induced dual signal amplification strategy based on cascade-type catalytic reactions. Issue 8 (16th March 2016) - Li, Suping; Lai, Jianping; Qi, Liming; Saqib, Muhammad; Majeed, Saadat; Tong, Yuejing; Xu, Guobao
Abstract : A simple and fast colorimetric method is developed for the sensitive and selective detection of Hg 2+ based on a dual signal amplification strategy. Abstract : A simple and fast colorimetric method is developed for the sensitive and selective detection of Hg 2+ based on a dual signal amplification strategy: in situ Hg 2+ induced catalytic synthesis of oxidase-like AuHg nanoparticles and subsequent catalytic oxidation of TMB by AuHg nanoparticles.